2008
DOI: 10.1111/j.1365-2982.2008.01164.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous electroacupuncture improves dyspeptic symptoms and increases high frequency heart rate variability in patients with functional dyspepsia

Abstract: The aim of the study was to evaluate the therapeutic value and possible mechanisms of transcutaneous electroacupuncture (TEA) in a double-blind and cross-over study in patients with functional dyspepsia (FD). Twenty-seven patients with FD were enrolled and the study consisted of two parts: (i) acute effects of TEA at PC6 and ST36 on gastric slow waves and heart rate variability and (ii) chronic (2 weeks) effects of TEA at PC6 and ST36 on dyspepsia symptoms, gastric slow waves, heart rate variability and neurop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
156
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(162 citation statements)
references
References 28 publications
6
156
0
Order By: Relevance
“…Few studies confirm the effectiveness of hypnotherapy, although their results suggest that hypnotherapy may be more effective than drug therapy for the treatment of FD [71]. One study showed the efficacy of transcutaneous electroacupuncture in the treatment of FD [72], but in another study the results of classical six-point manual acupuncture could not be differentiated from the placebo [73]. Neither transcutaneous electroacupuncture nor manual acupuncture is widely practiced in Japan, and no studies have been reported.…”
Section: Treatmentmentioning
confidence: 95%
“…Few studies confirm the effectiveness of hypnotherapy, although their results suggest that hypnotherapy may be more effective than drug therapy for the treatment of FD [71]. One study showed the efficacy of transcutaneous electroacupuncture in the treatment of FD [72], but in another study the results of classical six-point manual acupuncture could not be differentiated from the placebo [73]. Neither transcutaneous electroacupuncture nor manual acupuncture is widely practiced in Japan, and no studies have been reported.…”
Section: Treatmentmentioning
confidence: 95%
“…[35][36][37] EA at ST36 improved the percentage of normal gastric slow waves as well as the percentage of tachygastria in healthy volunteers. 38 Liu et al 21 reported that 2-week TEA at ST36 decreased dyspepsia symptoms and elevated vagal activity in patients with functional dyspepsia. Two-week daily TEA at ST36 improved GI symptoms and quality of life in systemic sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…These parameters were previously shown to be effective in treating GI symptoms in patients with gastroparesis, scleroderma and functional dyspepsia. 7,8,12,[19][20][21][22] Measurements of electrogastrography and electroencephalography Recording and analysis of the electrogastrography. A noninvasive method similar to electrocardiography, called electrogastrography, was used in this study.…”
Section: Transcutaneous Electroacupuncturementioning
confidence: 99%
“…Recent study showed that TENS applied to the acupuncture points (transcutaneous-EA; TEA) at the hands and lower legs improves GI symptoms in patients with FD [25] . Effects of acupuncture on GI motility is mediated via the CNS levels, not the spinal levels.…”
Section: Anti-stress Effects Of Somatosensory Stimulation 2-1 Effectmentioning
confidence: 99%